2024
DOI: 10.1021/jacs.3c14554
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism-Guided Discovery of Cleavable Comonomers for Backbone Deconstructable Poly(methyl methacrylate)

Kwangwook Ko,
David J. Lundberg,
Alayna M. Johnson
et al.

Abstract: The development of cleavable comonomers (CCs) with suitable copolymerization reactivity paves the way for the introduction of backbone deconstructability into polymers. Recent advancements in thionolactone-based CCs, exemplified by dibenzo[c,e]-oxepine-5(7H)-thione (DOT), have opened promising avenues for the selective deconstruction of multiple classes of vinyl polymers, including polyacrylates, polyacrylamides, and polystyrenics. To date, however, no thionolactone CC has been shown to copolymerize with metha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 109 publications
0
0
0
Order By: Relevance
“…A different DFT based workflow was recently reported by the team of Johnson to develop benzyl-functionalized thionolactones (bDOTs) that overcame a previous key limitation of thionolactones: copolymerization with methacrylates. [83] In contrast to defining a composite rate constant to cover the multistep radical addition process, the entire radical addition potential energy landscape was evaluated via DFT to identify the reactivity ratio defining key transition states (Figure 4A). These calculations indicated that the introduction of radicalstabilizing substituents onto the benzylic carbon of DOT may lower the energy of the rate-determining transition state of the DOT ring-opening, and thereby enable copolymerization with MMA (Figure 4B).…”
Section: Thionolactonesmentioning
confidence: 99%
“…A different DFT based workflow was recently reported by the team of Johnson to develop benzyl-functionalized thionolactones (bDOTs) that overcame a previous key limitation of thionolactones: copolymerization with methacrylates. [83] In contrast to defining a composite rate constant to cover the multistep radical addition process, the entire radical addition potential energy landscape was evaluated via DFT to identify the reactivity ratio defining key transition states (Figure 4A). These calculations indicated that the introduction of radicalstabilizing substituents onto the benzylic carbon of DOT may lower the energy of the rate-determining transition state of the DOT ring-opening, and thereby enable copolymerization with MMA (Figure 4B).…”
Section: Thionolactonesmentioning
confidence: 99%
“…In the context of ring-opening metathesis polymerization (ROMP), low-strain cyclic silyl ethers and enol ethers were recently reported by our groups to copolymerize with traditional norbornene-based monomers to yield deconstructable linear, graft, and thermoset copolymers. Similarly, cyclic disulfides, , isocyanides, and thioamides have recently emerged as competent cleavable comonomers with broad classes of vinyl monomers via radical polymerization. In this context, the distribution of these comonomers within a polymer backbone (i.e., the comonomer sequence) dictates degradation properties; thus, accurate understanding of comonomer reactivity is vital for predicting and engineering the end-of-life properties of these materials. , Finally, the emerging use of data-driven research practices in combination with machine learning methods relies on large bodies of accurate and high-quality data to develop broadly useful tools for property and reactivity predictions. …”
Section: Introductionmentioning
confidence: 99%